Rules and rituals in medieval power games a German perspective - Althoff, Gerd 1943- (Brill, 2020)
Part 1. Introduction -- What exactly are Spielregeln? -- Spielregeln and rituals -- Spielregeln, order of rank and conflicts -- Part 2. Rules -- Authority and violence of kings in tenth and eleventh century Germany -- Rules of conflict among the warrior aristocracy of the High Middle Ages -- Openness and secrecy : two fundamental categories of medieval communication -- Saxon bishops in the tenth and eleventh centuries : strategies and rules of their political activities -- The perspective of an expert : Gislebert of Mons --
Rezensiert in: Central European History 55 (2022), Heft 1, Seite [138]-139 (Len Scales, Durham University)
Keywords: Heinrich -- II. -- Heiliges Römisches Reich, Kaiser -- 973-1024; Friedrich -- I. -- Heiliges Römisches Reich, Kaiser -- 1122-1190; Geschichte 800-1200; Ritual; Politik; Deutschland; Political customs and rites / Germany / History / To 1500; Nobility / Germany / History / To 1500; Germany / Politics and government / 843-1273; Germany / Kings and rulers / History / To 1500; Germany / Church history / 843-1517